Produção de gérbera de corte (Gerbera jamesonii) em função de diferentes disponibilidades hídricas - Piroli, Jéssica Dariane (2018)
Gerbera is traditionally cultivated as a cut flower among the ornamental plants of major commercial importance in Brazil. However, this activity has been undergoing transformations, making the production chain increasingly competitive, requiring decision-making capacity, among them, the management of irrigation in a protected environment, since the production depends almost exclusively on water irrigation. In this sense, the aim of the present study was to determine the effects of water availability on gerbera by evaluating the production of floral stems in order to identify the appropriate management producing gerbera in pots. The experiment was conducted in an air-conditioned greenhouse at the Floriculture Department of the UFSM Polytechnic College, Santa Maria - RS. The experimental design was completely randomized, with five treatments, being 120%, 100%; 80%; 60% and 40% of the retention capacity of the vessel and ten replicates, vases with a capacity of 25 liters were used, where one molt was transplanted per vase, that is, each vase was an experimental unit, totaling 50 vases. The following variables were analyzed: culture coefficient (kc) for cutting gerbera, length of stems (cm); inflorescence diameter (cm); diameter of the stems (mm) and number of stems per plant. The results showed that the germination coefficient, cultivated in protected environment, was 0,72 in the vegetative period I, 0,81 in the vegetative period II, 0,85 in the flowering period I, 0,89 in the full bloom period II, 1,33 at full flowering III, and 1.06 at full flowering IV. Also, water availability of 80% or 100% is required to produce long stems with ideal inflorescence and rod diameters, which directly reflects on the quality of the final product. The maximum technical efficiency for the production of gerbera stems was observed for 79.3% of vessel retention capacity. The profit increases for all the values of commercialization of rods used, as the relation between the price of irrigation and product price decreases.